Analisis Model Pembelajaran Make A Match Terhadap Hasil Belajar Siswa - Homroul Fauhah; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This article aims to analyze how the learning model make a match to learningoutcoms in archival subjects, the basic competencies of various archival equipment. In the learning process of archiving equipment many teachers still use the direct learning model with the lecture method, this makes students bored and bored during the learning process, so that teachers need to vary the learning models that are fun and in accordance with learning so that the students are not bored and fed up. Make a match model is appropriate learning models to improve learning outcoms, because the make a match learning model can makestudents more aktive, develop student knowledge, be motivated, and interact with each other in cooperation so that it affects the student learning outcoms. This type of research is conceptual which proves that the make a match learning model can affect learningoutcoms.